Endometrial Histology of Depomedroxyprogesterone Acetate Users: A Pilot Study - Andrea Ries Thurman; David E. Soper (Hindawi Limited, 2006)
Objective. To obtain pilot data on the endometrial histology of Depomedroxyprogesterone acetate (Depo-Provera, DMPA) users experiencing breakthrough bleeding (BTB) versus users with amenorrhea. To compare the endometrial histology of patients who used DMPA continuously for 3-12 months versus those who used it for 13 months or more. Methods. Cross-sectional study. Endometrial biopsy was obtained from all consenting patients who used DMPA for at least 3 months. Patients were divided into those with BTB in the last 3 months versus those with amenorrhea for at least 3 months. Histology results and duration of therapy were compared. Results. The proportion of women with chronic endometritis, uterine polyps, atrophic, proliferative, or progesterone-dominant endometrium did not differ between those DMPA users with BTB versus those with amenorrhea. Duration of therapy did not correlate with symptoms of BTB or endometrial histology. Chronic endometritis was the most common histologic finding (10/40, 25%) and occurred more often in women experiencing BTB (35% versus 15%) (RR 1.62 CI 0.91-2.87). Moreover, 45% of women with BTB had received DMPA for more than 12 months. Conclusions. BTB was more common than previously reported in women using DMPA for more than 12 months. Chronic endometritis, which may indicate an underlying infectious or intracavitary anatomic etiology, has not been previously reported as a frequent finding in DMPA users, and may be related to ethnic or other sociodemographic characteristics of our patient population. Further study to elucidate the etiology of chronic endometritis in these patients is warranted.